2000
DOI: 10.1021/ac0027643
|View full text |Cite
|
Sign up to set email alerts
|

AC Educator: Cooperative student activities as learning devices.

Abstract: a c e d u c a t o rLearning needs to be conceived of as something a learner does, not something that is done to a learner (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This study further confirmed the findings of earlier researches with regards to the clear differences between the lecture method or "factory model" and collaborative learning. While traditional methods have little measurable effects on educational achievements of students (Hofstein, Lunetta, 1982), collaborative learning improves students' academic achievement, helps them develop better reasoning and critical thinking skills, ability to transfer prior knowledge to new situations, reduces stress levels, promotes more positive attitudes toward chemistry and improves student commitment and retention (Wenzel, 2007(Wenzel, , 2000(Wenzel, & 1998.…”
Section: Resultsmentioning
confidence: 99%
“…This study further confirmed the findings of earlier researches with regards to the clear differences between the lecture method or "factory model" and collaborative learning. While traditional methods have little measurable effects on educational achievements of students (Hofstein, Lunetta, 1982), collaborative learning improves students' academic achievement, helps them develop better reasoning and critical thinking skills, ability to transfer prior knowledge to new situations, reduces stress levels, promotes more positive attitudes toward chemistry and improves student commitment and retention (Wenzel, 2007(Wenzel, , 2000(Wenzel, & 1998.…”
Section: Resultsmentioning
confidence: 99%
“…To begin, as we noted previously, decades of research support the benefits of group learning. In addition, research, often from precollege educational settings, suggests that racially mixed cooperative learning groups increase learning and foster more positive interactions among people with different backgrounds (Johnson et al 1983;Slavin 1991;Wenzel 2000).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Classroom environments can be characterized as competitive, individualistic, or cooperative, with the first two far more common than the last (26). Competitive classroom environments do not generally reward students who are gentle, altruistic, and able to put the welfare of others over themselves (27)(28)(29).…”
Section: A C E D U C a T O Rmentioning
confidence: 99%